Ovariectomy-induced depressive-like behavior and brain glucose metabolism changes in female rats are not affected by chronic mild stress. (May 2020) - Khayum, M.A.; Moraga-Amaro, R.; Buwalda, B.; Koole, M.; den Boer, J.A.; Dierckx, R.A.J.O.; Doorduin, J.; de Vries, E.F.J.
Highlights: Short-term estrogen depletion in rats had a significant effect on brain metabolism in subcortical areas. Long-term estrogen depletion in rats resulted in depressive-like behavior and both increase and decrease of glucose metabolism in specific brain areas. Chronic mild stress (CMS) in rats did not influenced depressive-like behavior or changes in brain metabolism associated to estrogen depletion. Abstract: The increased incidence of depression in women going through peri-menopause suggests that fluctuations in estrogen levels may increase the risk of developing depression. Nonetheless, this psychiatric disorder is likely to be multifactorial and consequently an additional trigger may be needed to induce depression in this population. Stress could be such a trigger. We therefore investigated the effect of ovarian estrogen depletion and chronic mild stress (CMS) on depressive-like behavior and brain metabolism in female rats. Approximately 2 and 9 weeks after estrogen depletion by ovariectomy, behavioral changes were assessed in the open-field test and the forced swim test, and brain metabolism was measured with [ 18 F]FDG PET imaging. A subset of animals was subjected to a 6-weeks CMS protocol starting 17 days after ovariectomy. Short-term estrogen depletion had a significant effect on brain metabolism in subcortical areas, but not on behavior. Differences in depressive-like behavior were only found after prolonged estrogen depletion, leading to an increased immobility time in the forced swim test. Prolonged estrogen depletion also resulted in an increase in glucose metabolism in frontal cortical areas and hippocampus, whereas a decrease glucose metabolism was found in temporal cortical areas, hypothalamus and brainstem. Neither short-term nor prolonged estrogen depletion caused anxiety-like behavior. Changes in body weight, behavior and brain glucose metabolism were not significantly affected by CMS. In conclusion, ovarian estrogen depletion resulted in changes in brain metabolism and depressive-like behavior, but these changes were not enhanced by CMS.